2020
DOI: 10.1111/1749-4877.12467
|View full text |Cite
|
Sign up to set email alerts
|

Density‐induced social stress alters oxytocin and vasopressin activities in the brain of a small rodent species

Abstract: It is known that social stress could alter oxytocin (OT) and arginine‐vasopressin (AVP) expression in specific regions of brains which regulate the aggressive behavior of small rodents, but the effects of density‐induced social stress are still unknown. Brandt's voles (Lasiopodomys brandtii) are small herbivores in the grassland of China, but the underlying neurological mechanism of population regulation is still unknown. We tested the effects of housing density of Brandt's voles on OT/AVP system with physical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
27
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 17 publications
(31 citation statements)
references
References 35 publications
4
27
0
Order By: Relevance
“…In this study, we found that, in two eld experiments, high population density was associated with increased AVP/AVPR expression, and decreased the OT/OTR expression, which correspond well to the increased frequency of aggression and chasing behaviors. These results are exactly consistent with our previous study under laboratory condition [12]. In another study, we found aggression of Brandt's voles was reduced by injection of OT but increased by injection of OT antagonists and OTR antagonists [24].…”
Section: Discussionsupporting
confidence: 93%
See 4 more Smart Citations
“…In this study, we found that, in two eld experiments, high population density was associated with increased AVP/AVPR expression, and decreased the OT/OTR expression, which correspond well to the increased frequency of aggression and chasing behaviors. These results are exactly consistent with our previous study under laboratory condition [12]. In another study, we found aggression of Brandt's voles was reduced by injection of OT but increased by injection of OT antagonists and OTR antagonists [24].…”
Section: Discussionsupporting
confidence: 93%
“…crowding or aggression, food or space shortage). Our previous study indicated that high housing density could decrease OT or its receptor but increase AVP of its receptors [12], but it is not clear whether such associations operate in eld conditions. In this study, we showed that high population density increased AVP/AVPR expression but decreased the OT/OTR expression, and aggression behavior of voles was also increased in semi-natural conditions.…”
Section: Discussionmentioning
confidence: 93%
See 3 more Smart Citations